The Effect of Accounting Conservatism, Capital Intensity and Independent Commissionerson Tax Avoidance, With Independent Commissioners as Moderating Variables (Empirical Study on Banking Companies on the IDX 2014-2017) - Lismiyati, Nunik; Herliansyah, Yudhi (Dinasti Publisher, 2021)
This study aims to provide empirical evidence that accounting conservatism, capital intensity and Independent Commissioners have an effect on tax avoidance, as well as the existence of an independent board of commissioners as a moderating variable to interact with the relationship between accounting conservatism and capital intensity on tax avoidance. The method used is descriptive quantitative. The sample of this research is on 30 banking companies on the Indonesian Efex Exchange for 2014-2017 and the data analysis technique used is SPSS 22.The results of this study indicate that accounting conservatism, capital intensity has a significant effect on tax avoidance, and independent board of commissioners has no effect on tax avoidance. tax avoidance, and the independent board of commissioners did not moderate accounting conservatism on tax avoidance, while the independent board of commissioners was a variable that moderated capital intensity on tax avoidance.